If x k y h = ( x + y ) k + h , where k and h are constants, find d x d y .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The question is a little over-complicated, but the above is a great solution.
Let us try to find a = y / x for any given x . ie y = a x
x h ( a x ) k = x h + k ( 1 + a ) h + k
a k = ( 1 + a ) h + k . ie a is independent of x , y ,
ie a is constant, y = a x , for all valid x .
So actually all the possible outcomes of the original equation are straight lines!
And d y / d x = a , a constant for any given ( h , k ) . Calling it y / x suggests it varies with x , but it does not!
Let y = v x . Substituting in the given equation, we have x k ( v x ) h = ( x + v x ) k + h , or v h = ( v + 1 ) k + h . So v is constant, independent of h and k . So d x d y = v = x y .
Problem Loading...
Note Loading...
Set Loading...
x k y h k x k − 1 y h + h x k y h − 1 d x d y x k x k y h + y h x k y h d x d y x k + y h d x d y ( y h − x + y k + h ) d x d y ( y ( x + y ) h x − k y ) d x d y ⟹ d x d y = ( x + y ) k + h = ( k + h ) ( x + y ) k + h − 1 ( 1 + d x d y ) = x + y k + h x k y h ( 1 + d x d y ) = x + y k + h ( 1 + d x d y ) = x + y k + h − x k = x ( x + y ) h x − k y = x y Differentiate both sides w.r.t. x Note that x k y h = ( x + y ) k + h Divide both sides by x k y h Rearrange